(untitled) (Journal on Excellence in College Teaching, 2024)
Non-tenure-track faculty have become the “new faculty majority,” and it is clear that they face challenges and needs quite different from tenure-track faculty. This study reports how the results of a needs assessment guided an institutional effort to address these needs with a cohort-based faculty learning community (FLC) for adjunct faculty. The year-long “adjunct FLC” is described, and results of a program evaluation are reported. Findings support the efficacy of the FLC approach for building a community of collaborative learning and making adjunct faculty feel less isolated and more like vital, appreciated members of the academic community.